Analysis of Paulo Freire’s influence on productions of graduate schools of the Federal University of Santa Maria (2009-2018) (Research, Society and Development, 2020)
The educator Paulo Freire presents a relevant legacy, especially when it comes to teacher training and a pedagogy that is critical and transformative. Due to the prominence of the research produced at the Federal University of Santa Maria (UFSM), the objective of this work was to analyze the presence and influence of Freire in the Master and Doctorate productions of the institution, from 2009 to 2018, using the content analysis as a methodology. Six questions were employed for the quantitative and qualitative characterization of the works. 64 dissertations and 10 theses were found, most of which were concentrated in the Graduate Program in Education (PPGE), but also present in areas such as Psychology, Communication and even Economics. Most of the works were developed in a theoretical and practical way, being applied in schools and having the educators as research subjects. The main theorists used alongside Paulo Freire were Miguel G. Arroyo, Antonio Sampaio da Nóvoa, Maurice Tardif and Francisco Imbernón. The most developed categories related to Freire's thought were dialogue/dialogicity; teacher training; problematization and praxis. It is concluded that Freire's thinking remains present and influential in academic productions and it is hoped that these analyzes can guide educators and students in their studies, in order to further spread the pedagogical thinking proposed by Paulo Freire.